PENGEMBANGAN MODUL PENCEMARAN LINGKUNGAN BERBASIS KEMAMPUAN MEMECAHKAN MASALAH TERINTEGRASI NILAI-NILAI ISLAM - Annisa; Kartika Manalu; Rohani (Jurnal Bionatural, 2024)
This research aims to determine the feasibility of an environmental pollution module based on the ability to solve problems integrated with Islamic values and to determine students' responses to the environmental pollution module based on the ability to solve problems integrated with Islamic values. Product development design uses the Borg & Gall model with eight stages including, potential and problems, data collection, product design, product validation, product revision, product testing, product revision, and final product. This research was carried out from September-November 2022 with a research sample of 30 class X students at MA Al-Ikhlas Kebun Ajamu. The results of this research show that the percentage meets the appropriate category with an average score obtained in each aspect, namely 81% by material experts, 85% by media experts, 82% by religious experts, 87% by biology teachers, and 89% by students. So it can be concluded that the environmental pollution module teaching materials based on problem-solving abilities integrated with Islamic values are suitable for use for teaching and learning activities.